Strategi Pembelajaran di Masa Pandemi Covid-19 pada Satuan Menengah di Provinsi Jawa Tengah - Hayuning Santa Sisilia; Retno Sunu Astuti; Budi Puspo Priyadi; Augustin Rina Herawati; Teuku Afrizal (Universitas Medan Area, 2022)
This study aims to find, understand, explain and obtain an overview of the strategies carried out in the implementation of Learning during the Covid-19 Pandemic at the Secondary Education Unit in Central Java Province which is then expected to be able to analyze and describe the implementation and make recommendations on policy models to overcome learning problems. during the Covid-19 Pandemic. The results of this study were carried out through Strengthening Communication Facilities and Learning Content Creation, Strengthening in Learning Methods, through hybrid learning by combining several aspects, and Partnerships, through collaboration with the private sector and parents of students.